Analysis Of Human Traits Variation Through Genetic Discs Based On Phenotype Frequency, Allele Frequency, And Genetic Index - Muhsin Chatib (EDUJAVARE: International Journal of Educational Research, 2026)
This study aimed to analyze human phenotypic variation using a genetics wheel, based on phenotype frequencies, allele frequencies, and genetic indices. A quantitative descriptive approach was employed through a genetics practical activity involving 39 students from the Biology Education Study Program. The traits observed included tongue-rolling ability, earlobe shape, thumb shape, presence of dimples, and hairline shape. Data were obtained through direct observation and subsequently analyzed using phenotype frequency percentages and allele frequencies based on the Hardy-Weinberg principle. The results indicated that the free earlobe trait exhibited the highest dominant phenotype frequency (92.30%), while the straight hairline exhibited the highest recessive phenotype frequency (79.49%). Allele frequencies varied across traits, with dominant allele (p) values ​​ranging from 0.12 to 0.74 and recessive allele (q) values ​​ranging from 0.26 to 0.88. Genetic index analysis revealed variations in phenotypic trait combinations among individuals, with a genetic index of 24 being the most frequently observed (20.51%). The findings demonstrate that the student population possesses a relatively high level of phenotypic diversity, suggesting that practical activities using a genetics wheel can facilitate the understanding of trait inheritance and population genetics concepts.